City centre masterplanning and cultural spaces: a case study of Sheffield - Holmes, Kirsten; Beebeejaun, Y. (Palgrave, 2007)
This paper presents a case study of Sheffield city centre's masterplan, focusing on the Heart of the City civic core. Sheffield was one of the first city councils to use culture as a basis for economic regeneration. The literature argues that while early regeneration was economically driven, under New Labour cultural planning has become more focused on creating inclusive spaces. The new developments in Sheffield associated with the masterplan have been in two stages. The first created award winning public cultural spaces, including the Millennium Galleries and Winter Garden. The second phase has led to private, commercial developments, which this paper argues have impacted negatively on the public spaces. The public spaces do not meet the inclusive aspirations of either Sheffield's local strategic partnership or cultural policy. The Sheffield case, however, demonstrates how all regeneration is located within local economic realities. As a secondary city within its region, in terms of office rents, there is a limit to what the public sector in Sheffield can demand from the private sector. The masterplan's developments are ongoing and there is evidence that as office rentals are increasing the public sector could exert more power in the future.